Transmission Precision Analysis of Planetary Line Gear Transmission based on Assembly Error - Ting Geng; Yuting Wei; Aiping Deng; Jiang Ding (Jixie chuandong)
Focusing on a planetary gear transmission that uses line gear as core transmission elements， and the influence of assembly errors on its transmission precision is studied. The structural composition of the line gear transmission and the characteristics of different transmission schemes are analyzed， the space meshing coordinate system for the gear train are established， and the quantitative relationship of the parameters at the meshing moment is established among the sun line gear， the outer ring line gear and the planetary line gear. The causes of the angle error and displacement error are analyzed， both between the planetary line gear and the sun line gear and between the outer ring line gear and the planetary line gear. Tooth Contact Analysis （TCA） is subsequently adopted to carry out the numerical analysis of the assembly errors model for the line gear transmission. The results show that， among assembly errors of the planetary gears， the angular errors of its rotation around the horizontal axis， the displacement errors in the longitudinal section of the outer ring line gear， and the displacement errors in the cross section of the planetary line gear， are of more effect on its transmission. That is of significant to design and assembly of the planetary gears.